If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2x+3=+6x-8
We move all terms to the left:
-2x+3-(+6x-8)=0
We add all the numbers together, and all the variables
-2x-(6x-8)+3=0
We get rid of parentheses
-2x-6x+8+3=0
We add all the numbers together, and all the variables
-8x+11=0
We move all terms containing x to the left, all other terms to the right
-8x=-11
x=-11/-8
x=1+3/8
| 13-8+x=5 | | 14x+11=15x-5 | | -16=5n+3n | | x2x7Y=x | | -4(x+3)57=-35 | | 3w-75=370 | | x+4+3x-1+90=180 | | 3x-70=380 | | 22x-32=74 | | 12x=2^3+10 | | -1=-3a+4a | | (9x+5)=(8x+6) | | 10=2m-7m | | 66x+7=8x−15x+7=8x−156x+7=8x−15 | | 4r-6r=10 | | 7x-7+3x+7+90=180 | | 3x/10-4/5=x/2-3 | | 8x+2+7=1 | | 60+123+89+16=4c | | 45x+14x-1+63=180 | | 2x/3-5=8 | | 6+8x+7x=-9 | | 1/32862=b | | 7^(3x-4)=3^(4x) | | 4m=2m-4 | | 3x+5=9x-2 | | 7^3x-4=3^4x | | 20+6y=-10 | | 7^x^2=20.42 | | (-5/3)x=-25 | | 3(3x+2/3)=74 | | 5(x+5)=-15 |